2014
DOI: 10.1007/7653_2014_31
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approaches to Microvessel Analysis: Hotspots, Microvessel Density, and Vessel Proximity

Abstract: This chapter reviews the approaches that have evolved over the last several decades to make quantitative measurements related to vascularity and angiogenesis in histology tissue sections. The early work focused on hotspot analysis, measuring antibody stained vessels in areas of intense vasculature on a tissue section. With the advent of whole slide scanning, newer algorithms could perform whole tissue section analysis, and quantify vascularity across an entire tumor section or other larger region of a microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…There have been many attempts to help histopathologists in Ki-67 index quantification involving computers and digital versions of the glass slide, called the whole slide image (WSI). A review of papers concerning this subject published both in the days when only small images could be handled by computers [ 17 – 24 ] and nowadays when WSIs are available and computers or clusters of computers have the necessary computing power to manipulate them [ 25 34 ] shows that investigators propose the use of computers on at least 3 levels of the process of proliferation index quantification: (1) in region selection, (2) in immunopositive and immunonegative cell nuclei selection, and (3) in proliferation and other index counting. While the third level is obvious and the second is widely explored, the first level is still poorly represented in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many attempts to help histopathologists in Ki-67 index quantification involving computers and digital versions of the glass slide, called the whole slide image (WSI). A review of papers concerning this subject published both in the days when only small images could be handled by computers [ 17 – 24 ] and nowadays when WSIs are available and computers or clusters of computers have the necessary computing power to manipulate them [ 25 34 ] shows that investigators propose the use of computers on at least 3 levels of the process of proliferation index quantification: (1) in region selection, (2) in immunopositive and immunonegative cell nuclei selection, and (3) in proliferation and other index counting. While the third level is obvious and the second is widely explored, the first level is still poorly represented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…While the third level is obvious and the second is widely explored, the first level is still poorly represented in the literature. There are methods of region selection concerning Hematoxylin and Eosin staining [ 35 37 ], while for Ki-67 stained with DAB and counterstained by Hematoxylin there are the studies published by Potts [ 34 ] and coworkers, Lu and coworkers [ 35 ], and Gavrielides and coworkers [ 7 , 8 ]. The third group of investigators performed a pooling study and concluded that “… for validation study should be focused on specific pathology tasks to eliminate sources of variability that might dilute findings.” So, a validation study of a specific use of Digital Pathology, that is, in the quantification of the proliferation index based on Ki-67 used in meningiomas, is presented in this paper.…”
Section: Introductionmentioning
confidence: 99%